The path to extreme violence: Nazism and serial killers - Cotter, Philippe (Frontiers in Behavioral Neuroscience, 2010)
In people’s minds, extreme violence is an enigma. The tortures inflicted on defenceless victims seem to defy reason. Yet, the fact that these incidents keep recurring is proof that there are rules governing them. It is these rules that I have attempted to isolate. We shall see that they are clearly defined and that they are to be found in individual as well as collective violence. To categorise them is the first step towards implementing preventative measures which would help to protect the rational majority from a dangerous minority. Practice and theory are inextricably linked in the analysis of ‘organised insanity’ that is extreme violence.